2011
DOI: 10.1021/la2032576
|View full text |Cite
|
Sign up to set email alerts
|

Macroporous Polymers Obtained in Highly Concentrated Emulsions Stabilized Solely with Magnetic Nanoparticles

Abstract: Magnetic macroporous polymers have been successfully prepared using Pickering high internal phase ratio emulsions (HIPEs) as templates. To stabilize the HIPEs, two types of oleic acid-modified iron oxide nanoparticles (NPs) were used as emulsifiers. The results revealed that partially hydrophobic NPs could stabilize W/O HIPEs with an internal phase above 90%. Depending upon the oleic acid content, the nanoparticles showed either an arrangement at the oil-water interface or a partial dispersion into the oil pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 45 publications
3
53
0
Order By: Relevance
“…It is well known from the literature that in case of polymer composite systems, chemical composition, concentration, size and wettability of the nanoparticles directly affect the emulsion stability and the morphology of the final polymer product . Depending on the fact that emulsions are thermodynamically unstable, incorporation of nanoparticles into the continuous phase of an emulsion may lead to particle coagulation, which is the major factor influencing the stability of the emulsions by causing emulsion disintegration or phase inversion with heating.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known from the literature that in case of polymer composite systems, chemical composition, concentration, size and wettability of the nanoparticles directly affect the emulsion stability and the morphology of the final polymer product . Depending on the fact that emulsions are thermodynamically unstable, incorporation of nanoparticles into the continuous phase of an emulsion may lead to particle coagulation, which is the major factor influencing the stability of the emulsions by causing emulsion disintegration or phase inversion with heating.…”
Section: Resultsmentioning
confidence: 99%
“…[21,22] In this context, there are many examples of Pickering-polyHIPEs for diversified applications. For instance, carbon nanotubes, [27] oleic acid surface modified titania particles, [28] and iron oxide nanoparticles, [29] silane modified silica nanoparticles, [25] hydroxyapatite, [30] and cetyltrimethylammonium bromide modified graphen oxide have been used for the syntheses of Pickering-polyHIPEs. [31] Recently, porous TiO 2 materials made from Pickering-HIPEs for photocatalytic applications have been reported by Li et al [32] The aim of this study was to prepare novel polymer supports for photocatalytic water purification via emulsion templating.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the functional groups used for particle modification not only give desired properties to particles, but also enhance the emulsion stability. Accordingly, materials prepared with the use of these modified particles exhibits additional applications [15][16][17][18][19][20][21]. Until today, many research groups reported polyHIPEs prepared from Pickering HIPEs stabilized by various functionalized solid particles.…”
Section: Introductionmentioning
confidence: 99%